2014
DOI: 10.1111/tid.12249
|View full text |Cite
|
Sign up to set email alerts
|

Severe infections requiring intensive care unit admission in kidney transplant recipients: impact on graft outcome

Abstract: Sepsis was chiefly related to bacterial pneumonia or urinary tract infection. Pneumocystis jirovecii was the leading opportunistic agent, with a trend toward an increase over time. Infections often induced severe graft function impairment. Baseline creatinine and cyclosporine therapy independently predicted the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
2
19

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 41 publications
(50 reference statements)
1
37
2
19
Order By: Relevance
“…This finding is no different from other studies in this population, which report severe pulmonary complications more frequently after 6 months of transplantation, 8,9,16,18,23,24,27 although there are cases with different results. 17,28 Cardiogenic pulmonary edema is another condition often implicated in the genesis of ARF.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This finding is no different from other studies in this population, which report severe pulmonary complications more frequently after 6 months of transplantation, 8,9,16,18,23,24,27 although there are cases with different results. 17,28 Cardiogenic pulmonary edema is another condition often implicated in the genesis of ARF.…”
Section: Discussioncontrasting
confidence: 55%
“…21 It is important to note that although urinary infection is the most common in the renal transplant, 22 pulmonary infection is the main cause of sepsis and hospitalization in the ICU. 8,10,23,24 Traditionally, a greater number of infections are expected in the first 6 months of transplantation, a period in which immunosuppression is more intense. 25,26 However, it is interesting to note that patients included in this study had on average more than 5 years of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we consider that rituximab may induce earlyonset neutropenia in case 3 [21]. The characteristics of Although UTI was the leading cause of bacteremia, respiratory tract infections were the primary cause of infections requiring ICU admission (accounted for 54 %) in KTR [22]. In our current cohort, both recipients who developed pneumonia were in septic shock and died subsequently.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, a recent study showed that ICU-requiring severe infections in KTR had a significant impact on kidney allograft function. In particular, 47 % of the recipients who were alive had recovered their previous graft function, and 31 % had impaired graft function, including 19 % who were dependent on renal replacement therapy 90 days after ICU discharge [22]. In our current study, 3 recipients who required ICU admission died of infections.…”
Section: Discussionmentioning
confidence: 91%
“…Infectious diseases are the most common causes of pulmonary complications. Pulmonary infections are the main cause of acute respiratory failure (7) and severe sepsis (10)(11)(12), while community-acquired pneumonia is the leading cause of admission to the intensive care unit (ICU) (13). The incidence of neoplasia and drug-related pulmonary toxicity is lower (7,14,15).…”
Section: Introductionmentioning
confidence: 99%